Heavy social networking and online compulsive buying: the mediating role of financial social comparison and materialism. Issue 2 (3rd April 2022) - Pahlevan Sharif, Saeed; She, Long; Yeoh, Ken Kyid; Naghavi, Navaz
ABSTRACT: This study aimed to investigate the mediating role of financial social comparison and materialism in the relationship between heavy social networking and online compulsive buying among Malaysian young adults. A total of 1, 109 social networking sites users aged 16 to 25 years ( M = 20.57, SD  = 1.47), 87.9% Malaysian Chinese, completed an online survey questionnaire. Covariance-based structural equation modeling was used to assess the measurement model and the proposed serial mediation model. There was a significant positive relationship between heavy social networking and financial social comparison, financial social comparison and materialism, as well as materialism and online compulsive buying. Moreover, the results showed that financial social comparison and materialism mediated the relationship between heavy social networking and online compulsive buying. The findings shed light on the underlying mechanisms that drive the tendency for online compulsive buying. Several practical implications in terms of addressing the problem of online compulsive buying, not merely among young adults but also across the wider population were discussed.